2018
DOI: 10.1007/s12026-018-8996-5
|View full text |Cite
|
Sign up to set email alerts
|

Global report on primary immunodeficiencies: 2018 update from the Jeffrey Modell Centers Network on disease classification, regional trends, treatment modalities, and physician reported outcomes

Abstract: Primary immunodeficiencies (PI) are genetic defects of the immune system that result in chronic, serious, and often life-threatening infections, if not diagnosed and treated. Many patients with PI are undiagnosed, underdiagnosed, or misdiagnosed. In fact, recent studies have shown that PI may be more common than previously estimated and that as many as 1% of the population may be affected with a PI when all types and varieties are considered. In order to raise awareness of PI with the overall goal of reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
137
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 29 publications
3
137
1
5
Order By: Relevance
“…Ataxia‐telangiectasia is reported all over the world with an estimated prevalence of 1:40 000 to 1:100 000 . ATM deficiency is the second most common monogenic PID after familial Mediterranean fever with 2,514 globally reported patients (1,262 in North America, 251 in Latin America, 696 in Europe, 199 patients in Asia and Oceania, 106 patients in Africa) …”
Section: Introductionmentioning
confidence: 99%
“…Ataxia‐telangiectasia is reported all over the world with an estimated prevalence of 1:40 000 to 1:100 000 . ATM deficiency is the second most common monogenic PID after familial Mediterranean fever with 2,514 globally reported patients (1,262 in North America, 251 in Latin America, 696 in Europe, 199 patients in Asia and Oceania, 106 patients in Africa) …”
Section: Introductionmentioning
confidence: 99%
“…Predominantly antibody deficiencies are the most frequent type of primary immunodeficiency disorders (PIDs), with more than 13,000 symptomatic patients registered globally (~20% of all reported PID patients to date) [2]. Selective immunoglobulin A deficiency (SIgAD), the most prevalent of PID, is characterized by decreased serum IgA level lower than 7 mg/dL in individuals older than 4 years with normal levels of IgM and IgG in serum and exclusion of other causes of hypogammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Individual type of PIDs is considered to be rare in the population; however, recent studies have shown that PIDs may be more common than previously estimated 1% of the population when all varieties are combined [5]. The prevalence of PIDs varies depending on the type of immunodeficiencies and is difficult to be precisely calculated as the number of diagnosed cases is rapidly increasing.…”
Section: Prevalencementioning
confidence: 98%
“…The prevalence of PIDs varies depending on the type of immunodeficiencies and is difficult to be precisely calculated as the number of diagnosed cases is rapidly increasing. A 2018 global survey from the Jeffrey Modell Centers Network (JMCN) reported the case of PID patients followed in the JMCN increased by 35.4% to 102,097, while the case of patients identified with a specific gene defect increased 21.8% to 67,308 during the same period [5]. Up to 2018, 354 distinct disorders with 344 different gene defects were recognized [6].…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation